ATP citrate lyase activity is post‐translationally regulated by sink strength and impacts the wax, cutin and rubber biosynthetic pathways. (19th June 2014) - Xing, Shufan; van Deenen, Nicole; Magliano, Pasqualina; Frahm, Lea; Forestier, Edith; Nawrath, Christiane; Schaller, Hubert; Gronover, Christian S.; Prüfer, Dirk; Poirier, Yves
Summary Cytosolic acetyl‐CoA is involved in the synthesis of a variety of compounds, including waxes, sterols and rubber, and is generated by the ATP citrate lyase (ACL). Plants over‐expressing ACL were generated in an effort to understand the contribution of ACL activity to the carbon flux of acetyl‐CoA to metabolic pathways occurring in the cytosol. Transgenic Arabidopsis plants synthesizing the polyester polyhydroxybutyrate (PHB) from cytosolic acetyl‐CoA have reduced growth and wax content, consistent with a reduction in the availability of cytosolic acetyl‐CoA to endogenous pathways. Increasing the ACL activity via the over‐expression of the ACLA and ACLB subunits reversed the phenotypes associated with PHB synthesis while maintaining polymer synthesis. PHB production by itself was associated with an increase in ACL activity that occurred in the absence of changes in steady‐state mRNA or protein level, indicating a post‐translational regulation of ACL activity in response to sink strength. Over‐expression of ACL in Arabidopsis was associated with a 30% increase in wax on stems, while over‐expression of a chimeric homomeric ACL in the laticifer of roots of dandelion led to a four‐ and two‐fold increase in rubber and triterpene content, respectively. Synthesis of PHB and over‐expression of ACL also changed the amount of the cutin monomer octadecadien‐1, 18‐dioic acid, revealing an unsuspected link between cytosolic acetyl‐CoA and cutin biosynthesis. Together, these results reveal the complexity of ACL regulation and its central role in influencing the carbon flux to metabolic pathways using cytosolic acetyl‐CoA, including wax and polyisoprenoids.